PENINGKATAN AKTIVITAS DAN HASIL BELAJAR SISWA SMP MELALUI MODEL PEMBELAJARAN KOOPERATIF TIPE STUDENT TEAMS ACHIEVEMENT DIVISION DENGAN METODE EKSPERIMEN - Muhammad Dian Hadi Kesuma (Universitas Negeri Medan, 2013)
The objectives in these studies are (1) determine the activity of theeighth grade students of SMP 2 Labuan Deli in learning activities using an experimental method of inquiry. (2) Determine the increased student’s activityin class VIII of SMP Negeri 2 Labuan Deli in solving physics problems after applied the experimental method. This study is a classroom action research. Research subject is class VIII SMP 2 Semester 2 Labuan Deli T.P 2012/2013numbered 31 students consisting of 13 men and 18 women. Object of thisresearch is to apply the learning peruses STAD cooperative learning modelthrough experimental methods. This result show (1) There is an increase instudent learning outcomes Junior High School eighth grade 2 Labuan Deli isshown from: (a) the results of tests of student learning in the first cycle,namely: mean = 58.92 with the percentage of completeness = 19.36%; (b)tests of student learning outcomes in the second cycle is the average 75.70,percentage of completeness = 58.92%. Completeness percentage increased by61.24% and 0.41 normalized gain index or criteria being. (2) There is anincrease in the activity of the eighth grade students of SMP Negeri 2 LabuanDeli is shown from the first cycle only average 65.60 and 81.65 in the secondcycle. The results of this study can be used as input for teachers in an effort toincrease the activity and student learning outcomes by applying experimentalmethods.